2020
DOI: 10.1038/s41550-020-1123-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of green line emission in the dayside atmosphere of Mars from NOMAD-TGO observations

Abstract: The oxygen emission at 557.7 nm is a ubiquitous component of the spectrum of the terrestrial polar aurora and the reason for its usual green colour 1 . It is also observed as a thin layer of glow surrounding the Earth near 90 km altitude in the dayside atmosphere 2,3 but it has so far eluded detection in other planets. Here we report dayglow observations of the green line outside the Earth. They have been performed with the Nadir and Occultation for Mars Discovery ultraviolet and visible spectrometer instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 21 publications
(23 reference statements)
8
36
0
Order By: Relevance
“…Simulations of auroral electron impact on CO 2 , CO and O producing O( 1 S) indicate that collisions with CO 2 dominates over the other two processes. The oxygen 557.7-nm/297.2nm ratio of Einstein coefficients recommended by NIST is 16.4 (Kramida et al, 2019), and was recently confirmed by Gérard et al (2020), based on dayglow measurements on Mars from TGO-UVIS.…”
Section: Model Descriptionmentioning
confidence: 77%
“…Simulations of auroral electron impact on CO 2 , CO and O producing O( 1 S) indicate that collisions with CO 2 dominates over the other two processes. The oxygen 557.7-nm/297.2nm ratio of Einstein coefficients recommended by NIST is 16.4 (Kramida et al, 2019), and was recently confirmed by Gérard et al (2020), based on dayglow measurements on Mars from TGO-UVIS.…”
Section: Model Descriptionmentioning
confidence: 77%
“…(2018, 2020a) and Gérard et al. (2019, 2020). The sources of O( 1 D) in the Martian upper atmosphere are listed in Table 2.…”
Section: Model Simulations For Uvis Observing Conditionsmentioning
confidence: 97%
“…The methodology adopted for this study is similar to the approach described by Gérard et al. (2020). The TGO spacecraft is on a circular Martian orbit at ∼400 km inclined by 74° on the planetary equator since October 2016.…”
Section: Limb Observations Of Oxygen Linesmentioning
confidence: 99%
“…During the NOMAD-TGO observation period, the background intensity level around wavelength 6300 Å is equivalent to more than 10 kR. Moreover, the [OI] red-doublet emission lines are closer to the longer wavelength limit of the NOMAD-TGO instrument and the detector has a reduced sensitivity in this region, which is the main reason for the absence of these emissions in the observed dayside spectra (personal communication, Gérard et al, 2020). Furthermore, most of the NOMAD-TGO observations took place when Mars was moving away from the Sun.…”
Section: Effect Of Input Parameters On the Modelled Red-doublet Limb ...mentioning
confidence: 99%
“…The observation of [OI] 2972 Å emission has been done in the Martian upper atmosphere by several spacecraft-borne ultraviolet spectrometers starting from Mariner 6 to the recent MAVEN mission (Stewart, 1972;Leblanc et al, 2006;Jain et al, 2015). But the observation of [OI] 5577 Å emission had never been reported in the dayside of Martian upper atmosphere until the recent detection from Nadir and Occultation for Mars Discovery ultraviolet and visible spectrometer instrument on board the European Space Agency's Ex-oMars Trace Gas Orbiter (NOMAD-TGO) by Gérard et al (2020). Owing to its wide detection range (2000-6500 Å), this spectrometer is capable of observing the four forbidden atomic oxygen emissions ([OI] 2972, 5577, 6300, and 6364 Å) simultaneously in the Martian upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%